2003
DOI: 10.1097/01.ccm.0000059644.54819.67
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of decreased cortisol reserve in brain-dead potential organ donors

Abstract: Adrenal cortisol secretion after dynamic stimulation is deficient in a substantial proportion of brain-dead potential organ donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1
9

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 25 publications
1
40
1
9
Order By: Relevance
“…Patients' diagnoses were evenly distributed among groups. Even though it has been reported that in patients who had severe life-threatening illnesses at the time of death (24,25) or in brain-dead potential organ donors (26,27) serum ACTH and cortisol levels are controversial, ACTH overstimulation in vivo could not be discarded. In a previous study of 3␤-HSD mRNA expression in human adrenal tissues that we have published (4), tissue samples were obtained from similar sources.…”
Section: Discussionmentioning
confidence: 99%
“…Patients' diagnoses were evenly distributed among groups. Even though it has been reported that in patients who had severe life-threatening illnesses at the time of death (24,25) or in brain-dead potential organ donors (26,27) serum ACTH and cortisol levels are controversial, ACTH overstimulation in vivo could not be discarded. In a previous study of 3␤-HSD mRNA expression in human adrenal tissues that we have published (4), tissue samples were obtained from similar sources.…”
Section: Discussionmentioning
confidence: 99%
“…After brain death plasma levels of cortisol were significantly lower than in the patients who did not deteriorate to brain death, and 76% of the brain-dead patients did not respond to ACTH stimulation compared with 10% in the non-brain-dead group. 45 Thus, the prevalence of an attenuated adrenocortical response to physiologic concentrations of ACTH seems to be high in braindead patients, but its clinical implications are not settled. Corticoid treatment of brain-dead donors is routinely used by many centers, not to substitute adrenocortical failure, but to attenuate immune responses.…”
Section: Pulmonary Changesmentioning
confidence: 99%
“…44 Although plasma cortisol values remain within normal levels in most brain-dead donors, 34,35 the capacity to increase secretion upon ACTH stimulation seems to be reduced. 45 In a group of 37 patients with serious brain injury, 17 patients progressed to brain death. After brain death plasma levels of cortisol were significantly lower than in the patients who did not deteriorate to brain death, and 76% of the brain-dead patients did not respond to ACTH stimulation compared with 10% in the non-brain-dead group.…”
Section: Pulmonary Changesmentioning
confidence: 99%
“…However, neural influences or effects exerted by other circulating mediators cannot be excluded. Of interest, acute ACTH administration in brain-dead potential organ donors induced impaired cortisol release [40] . These results are consistent with downregulation of the ACTH receptor MC2R in the adrenal glands, i.e another peripheral melanocortin receptor.…”
Section: Discussionmentioning
confidence: 99%